Effect of low dose phenylephrine infusion on shivering and hypothermia in patients undergoing cesarean section under spinal anesthesia: a randomized clinical trial. (May 2022) - Palanisamy, S.; Rudingwa, P.; Panneerselvam, S.; Satyaprakash, M.V.S.; Kuberan, A.; Amala, R.
Highlights: Shivering is common after spinal anesthesia for cesarean section. Hypothermia is caused by redistribution of core heat to the periphery. Prophylactic phenylephrine infusion to reduce shivering was compared with placebo. Low-dose phenylephrine infusion lowered the incidence and severity of shivering. The core temperature decrease was less in patients receiving phenylephrine. Abstract: Background: Shivering is a common complication of spinal anesthesia. Phenylephrine, due to its peripheral vasoconstrictive effect, may limit the core to periphery redistribution of body temperature following spinal anesthesia, and reduce hypothermia and shivering. We hypothesized that prophylactic phenylephrine infusion would reduce shivering and hypothermia in women undergoing cesarean section under spinal anesthesia. Methods: A two-arm randomized, double-blind, placebo-controlled trial in term pregnant patients undergoing cesarean section. In the phenylephrine group (n=75) prophylactic phenylephrine infusion was administered at 25 µg/min immediately after initiation of spinal anesthesia and continued until the end of the operative period. In the placebo group (n=75) a normal saline infusion was administered during the same period. The primary outcome was the incidence of shivering; secondary outcomes were severity of shivering, changes in nasopharyngeal (core) temperature, and incidence of hypotension and bradycardia. Results: The incidence of shivering in the phenylephrine and control groups was 24.0% (95% CI 14.3% to 33.7%) and 53.3% (95% CI 42.0% to 64.6%), respectively. The severity of shivering was greater in the control group ( P =0.002) and the mean (±SD) end of surgery core temperature was significantly higher in the phenylephrine group (35.84°C ± 0.60) compared with controls (35.61°C ± 0.48) ( P =0.009). The incidence of hypotension was higher in controls (53.4% vs. 2.7%; P <0.001) but bradycardia more frequent in group P ( P =0.023). Conclusion: The incidence of shivering and degree of hypothermia were significantly reduced by a prophylactic phenylephrine infusion during cesarean section under spinal anesthesia.